Synthesis of the First Representatives of Spiro-1λ6-isothiazolidine-1,1,4-triones - Dobrydnev, Alexey V.; Popova, Maria V.; Saffon-Merceron, Nathalie; Listunov, Dymytrii; Volovenko, Yulian M. (Synthesis, 2015)
A strategy for the construction of spiro[cycloalkane-1,3′-1′λ6-isothiazolidine]-1′,1′,4′-triones through the sulfonylation of 1-aminocyclopropane- and 1-aminocyclobutanecarboxylates with methanesulfonyl chloride followed by alkylation with methyl iodide and subsequent cyclization in the presence of potassium tert-butoxide in N,N-dimethylformamide is reported. An efficient synthesis of starting 1-aminocyclopropane- and 1-aminocyclobutanecarboxylic acids was developed. The reaction of spiro[cycloalkane-1,3′-1′λ6-isothiazolidine]-1′,1′,4′-triones with N,N-dimethylformamide dimethyl acetal (DMFDMA) gives 5′-[(Z)-(dimethylamino)methylene]spiro[cycloalkane-1,3′-1′λ6-isothiazolidine]-1′,1′,4′-triones, the structure of which was confirmed by X-ray diffraction study.
Keywords: amino acids; sulfonamides; spiro compounds; cyclization; X-ray structure determination